An investigation of calcium-independent phospholipase A2 (iPLA2) and cytosolic phospholipase A2 (cPLA2) in schizophrenia. (March 2019) - Xu, Chuangye; Yang, Xuhan; Sun, Liya; Yang, Tianqi; Cai, Changqun; Wang, Peng; Jiang, Jie; Qing, Ying; Hu, Xiaowen; Wang, Dandan; Wang, Pengkun; Cui, Gaoping; et al.
Highlights: The plasma concentration of iPLA2 was increased in schizophrenia while cPLA2 not. Meta-analysis showed the iPLA2 in schizophrenia was increased while cPLA2 was not. The correlation between the iPLA2 and skin flushing response was positive. Abstract: Evidence indicates that abnormal phospholipase A2 (PLA2) levels and niacin insensitivity are present in individuals with schizophrenia. This study was designed to determine whether differences in plasma calcium-independent phospholipase A2 (iPLA2) and cytosolic phospholipase A2 (cPLA2) exist between those with schizophrenia and healthy controls, and to explore the correlation between PLA2s and the niacin skin reaction in schizophrenic patients. We performed ELISA experiments to measure the concentrations of plasma iPLA2 and cPLA2 and we conducted a series of niacin skin tests on schizophrenic patients from the Chinese Han population. In addition, a meta-analysis of the relationship between PLA2 and schizophrenia was conducted. The plasma concentration of iPLA2 in patients with schizophrenia was significantly higher than that in healthy controls while the plasma concentration of cPLA2 did not differ. The meta-analysis also revealed that the activity level of iPLA2 in individuals with schizophrenia was higher than that in healthy controls, whereas that of cPLA2 was not. Furthermore, a significant positive correlation was found between the concentration of iPLA2 and the score for the skin flushing response within 20 min. The abnormal plasma iPLA2 concentration and its relationship with the niacin skin test in schizophrenic patients has contributed to a deeper understanding of the pathology of schizophrenia, which may in turn provide new insights into the clinical diagnoses and treatment of schizophrenia.